Macaque remains from the early Pliocene of the Iberian Peninsula. Issue 123 (October 2018) - Alba, David M.; Delson, Eric; Morales, Jorge; Montoya, Plini; Romero, Gregorio
Abstract: Macaques dispersed out of Africa into Eurasia in the framework of a broader intercontinental faunal exchange that coincided in time with the sea level drop associated with the Messinian Salinity Crisis. They are first recorded in Europe (Italy and Spain) by the latest Miocene, being subsequently recorded all over Europe, albeit sparsely, throughout the Pliocene and Pleistocene. These fossil European macaques are attributed to several (sub)species of the extant Barbary macaque ( Macaca sylvanus ). In Iberia, fossil macaques are best documented by Macaca sylvanus florentina from various Early Pleistocene sites, whereas their published Pliocene record is very scarce. Here we report the oldest post-Messinian occurrence of macaques in the Iberian Peninsula, based on the description and metrical comparisons of two upper teeth (a male canine and a third molar of two different individuals) from the early Pliocene (MN14, 5.0–4.9 Ma) site of Puerto de la Cadena (Murcia, SE Spain). The male C 1 is fully comparable in morphology with those of extant and fossil M. sylvanus, and larger than those of Mesopithecus . The M 3, in turn, displays the typical papionin morphology that characterizes the dentally-conservative genus Macaca —thereby discounting an alternate assignment to either the extinct colobine monkey Mesopithecus or the more dentally-derived papionin Theropithecus . Dental size and proportions of the M 3 further support an attribution to an extinct subspecies of M. sylvanus instead of the larger papionin Paradolichopithecus . Mostly on biochronologic grounds, the two macaque teeth from Puerto de la Cadena are here assigned to Macaca sylvanus cf. prisca, albeit tentatively, given the lack of clear-cut criteria to distinguish this subspecies from the younger Macaca sylvanus florentina . The described material represents the oldest well-dated Pliocene record of macaques in Iberia, predating the record of Paradolichopithecus by almost 1.5 million years.